Indigenous economy in the Arctic regions: traditions, market, state (on the example of the transformation of the economic activity of the Indigenous peoples in Russia, Finland, and the USA) - Elena Gladun; Soili Nysten-Haarala; Svetlana Tulaeva; Olga Zakharova (Journal of Economic Sociology, 2022)
The article describes the interaction of the economy and culture, in the frameworks of Indigenous economic development. It implies strong embeddedness of the economic activities of Indigenous peoples in their social and cultural life. The Indigenous economy is based on traditional nature management and it is closely linked to their knowledge of nature, folklore, language, social norms and expectations. At the same time, the active inclusion of Indigenous communities into market relations leads to significant social and economic transformations of their lives. This implies the question of how to preserve the unique  indigenous culture in the market context. The paper considers three different scenarios for the development of the Indigenous economy in the Arctic regions using the examples of Russia, Finland and the United States. In Russia, the state plays a significant role by providing paternalistic care to the Indigenous population and focusing on the preservation of traditional culture; Finland is dominated by a market scenario for the development of Indigenous traditional economies and governmental support for indigenous culture and welfare; and the United States represents an intermediate case in which market incentives and paternalism are combined. The article also examines how the chosen scenario affected the social and cultural aspects of the life of the Indigenous people. The latter are associated with a new attitude to nature, the development of new cultural patterns, and the emergence of new culturally colored types of economic activity. The study is based on qualitative methodology. The main research methods were semi-structured interviews, observations, and analysis of documents.